Current Pattern in Antimicrobial Susceptibility in Enteric Fever In A Private Medical College (Bangladesh Journal of Medical Science, 2013)
Background and objectives: Enteric fever continues to be an important health problem in Bangladesh. Emerging drug resistance adds magnitude to this problem. Only surveillance studies can help form guidelines for therapy under such a situation. The present study was undertaken to determine the current pattern in antimicrobial susceptibility of enteric fever cases in a private medical college and to find out the incidence of multidrug resistant (MDR) cases. Study design: Hospital based observational study. Study setting and period: Medicine units of Ibn Sina Medical College hospital from october11 to august12. Source of materials/participants: Fever cases with clinical diagnosis of enteric fever and positive blood culture, attending the outpatient and admitted at hospital were included in the study. Susceptibility of the isolates to commonly available antibiotics were recorded. Treatment and responses were followed up. Results: 100 adult patients with fever had positive blood cultures were included in the study. Majority of patients were 19 30 yr olds (63%). Susceptibility of the isolates were tested against 14 available antibiotics. Ceftriaxone was sensitive in 99% cases followed by ciprofloxacin (96%), Gentamycin ( 96%) and cefixime (91%). Adeclining trend in sensitivity to Azithromycin ( 61%) was observed. Resurgence of chloramphenicol (81%) and cotrimoxazole (75%) sensitivity was noted. In 98 cases sensitivity to all three (amoxicillin, co-trimoxazole and chloramphenicol) were tested. 13 cases were found resistant to all the three drugs (13/98=13.2%). These MDR cases were sensitive to ceftriaxone (100%), cefixime (100%), azithromycin (100%), gentamycin(94%)and ciprofloxacin (88%). Conclusion: Antibiotic sensitivity pattern showed a trend with onset of emerging resistance to azithromycin (ceftriaxone vs azithromycin z value = 7.63; P value =0.001 (Significant) and azithromycin vs ciprofloxacin Z value = 6.66; P value =0.001 (Significant). Multidrug resistant cases present showed reduced susceptibility to gentamycin. Sensitivity of these drugs must be preserved through constant surveillance and use only under a protocol. DOI: http://dx.doi.org/10.3329/bjms.v13i1.17440 Bangladesh Journal of Medical Science Vol. 13 No. 01 January2014: 67-69